Simultaneous Determination of Two Groups of Elements in Milk by Electrothermal Atomic Absorption Spectrometry: Evaluation of Ruthenium Modifiers - Freschi, Gian Paulo G. [UNESP]; Freschi, Carolina D. [UNESP]; Gomes Neto, José Anchieta [UNESP] (Perkin-elmer Corp, 2009)
Different kinds of ruthenium coatings are proposed as chemical modifiers for the simultaneous determination of two groups of elements: first, the more Volatile elements Such as As, Bi, Pb, Sb, and Se and, second, the elements Co, Cr, Cu, Fe, and Mn in milk samples by electrothermal atomic absorption spectrometry. Uncoated and coated platforms tube with Ru modifiers and co-injection of Pd+Mg were Studied. Milk samples were 1 + 9 diluted in 1.0% (v/v) HNO(3) an injected into the tube. Very long tube lifetimes were obtained for the two groups with around 750 cycles for the direct determination of the diluted milk sample. Platforms, pretreated with W-Ru, were selected for the first group and pretreated platforms with W plus RuCl(3) were selected for the second group. Calibration by matrix matching and analytical curves in the 5.0 - 20.0 mu g L(-1) range with good linear correlation coefficients were obtained. Relative standard deviations were 7.2% and the calculated characteristic masses were between 7.2 pg and 89.1 pg. The limits of detection obtained for undiluted milk samples were as follows:For Group I elements:32 mu g L(-1) for As; 36 mu g L(-1) for Bi; 29 mu g L(-1) for Se; 29 mu g L(-1) for Sb; 25 mu g L(-1) for Pb; 18 mu g L(-1) for Co.For Group 2 elements:13 mu g L(-1) for Cr; 16 mu g L(-1) for Cu; 53 mu g L(-1) for Fe; 20 mu g L(-1) for Mn.